Predictors of procedural errors in class II resin composite restorations using bitewing radiographs - Abdulrahman A. Balhaddad; Nawaf AlGhamdi; Mohammed Alqahtani; Osama A. Alsulaiman; Ali Alshammari; Malik J. Farraj; Ahmed A. Alsulaiman (Saudi Dental Journal)
Objective: To identify the potential factors that induce procedural errors during posterior proximal resin composite restorations placed by dental students. Materials and Methods: This retrospective study evaluated 803 bitewing radiographs of posterior proximal resin composite restorations placed by dental students at Imam Abdulrahman bin Faisal University. Atypical radiographic signs of failure were screened, and different patient-, operator-, and clinical-related factors were recorded. Chi-square test was used to examine the relationship between procedural errors and recorded factors. Stepwise adjusted logistic regression model was performed to identify predictors of procedural errors. Results: The most observed errors were internal gaps at the bonding interface and internal voids. Molars had 0.39 the risk of internal voids (odds ratio [OR] = 0.39; confidence interval [CI] = 0.25–0.60; P = <0.0001), 0.41 the risk of sharp angle (OR = 0.41; CI = 0.24–0.68; P = <0.001), and 0.57 the risk of open contact (OR = 0.57; CI = 0.34–0.97; P = 0.04) compared to premolars. Those who were >40 years of age had 1.79 the risk of overhang compared to younger patients (OR = 1.79; CI = 1.04–3.11; P = <0.04). First molars and premolars had 0.64 the risk of overhang compared to second molars and premolars (OR = 0.64; CI = 0.41–1.00; P = 0.04). Junior students had 1.97 the risk of internal gap compared to their senior counterparts (OR = 1.97; CI = 1.20–3.21; P = 0.008). Mesial restorations had 0.38 the risk of external gap compared to mesio-occluso-distal (MOD) restorations (OR = 0.38; CI = 0.19–0.78; P = 0.003). Restorations with a margin coronal to the cemento-enamel junction (CEJ) had 0.44 the risk of external gap compared to those restorations with a margin apical to the CEJ (OR = 0.44; CI = 0.29–0.66; P = <0.0001). Conclusion: Our findings suggested a higher incidence of procedural errors in restoring premolars and MOD cavity preparations. Therefore, it is crucial to enhance the comprehensiveness of laboratory training and expose students to diverse clinical scenarios and various techniques.